Screening for medium chain acyl-CoA dehydrogenase deficiency using electrospray ionisation tandem mass spectrometry. Issue 2 (1st August 1998) - Clayton, Peter T; Doig, Mira; Ghafari, Soudabeh; Meaney, Cathy; Taylor, Catherine; Leonard, James V; Morris, Michael; Johnson, Andrew W
Abstract : OBJECTIVE: To establish criteria for the diagnosis of medium chain acyl-CoA dehydrogenase (MCAD) deficiency in the UK population using a method in which carnitine species eluted from blood spots are butylated and analysed by electrospray ionisation tandem mass spectrometry (ESI-MS/MS). DESIGN: Four groups were studied: (1) 35 children, aged 4 days to 16.2 years, with proven MCAD deficiency (mostly homozygous for the A985G mutation, none receiving carnitine supplements); (2) 2168 control children; (3) 482 neonates; and (4) 15 MCAD heterozygotes. RESULTS: All patients with MCAD deficiency had an octanoylcarnitine concentration ([C8–Cn]) > 0.38 μM and no accumulation of carnitine species > C10 or < C6 . Among the patients with MCAD deficiency, the [C8 –Cn] was significantly lower in children > 10 weeks old and in children with carnitine depletion (free carnitine < 20 μM). Neonatal blood spots from patients with MCAD deficiency had a [C8–Cn] > 1.5 μM, whereas in heterozygotes and other normal neonates the [C8–Cn] was < 1.0 μM. In contrast, the blood spot [C8–Cn] in eight of 27 patients with MCAD deficiency > 10 weeks old fell within the same range as five of 15 MCAD heterozygotes (0.38–1.0 μM). However, the free carnitine concentrations were reduced (< 20 μM) in the patients with MCAD deficiency but normal in the heterozygotes. CONCLUSIONS: Criteria for the diagnosis of MCAD deficiency using ESI-MS/MS must take account of age and carnitine depletion. If screening is undertaken at 7–10 days, the number of false positive and negative results should be negligible. Because there have been no instances of death or neurological damage following diagnosis of MCAD deficiency in our patient group, a strong case can be made for neonatal screening for MCAD deficiency in the UK.